2011
DOI: 10.1002/jemt.21052
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation in the human and mice cerebella after ketamine versus ketamine plus ethanol treatment

Abstract: To study the deleterious effects of ketamine and the potential interaction effects between ethanol and ketamine on the cerebellum, functional magnetic resonance imaging (fMRI) tests were performed on the habitual ketamine users (n = 3) when they flexed and extended their upper limbs. Another fMRI test was performed on the same participants in which they consumed alcohol (12%, 200 mL) 1 h before the test. Downregulation on the activity of cerebellum was observed and the level of activation in the cerebellum dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In fact, in the mice model, it had been documented both neurons and fibers (white matter) were both targets like in this report consisting of human subjects (Mak et al, 2010; Yeung et al, 2010b). Along with structural changes, fMRI and functional studies confirmed functional and cognitive derangements (Morgan and Curran, 2006; Sun et al, 2011, 2012; Chan et al, 2012; Yu et al, 2012). This human MRI brain imaging on the ketamine addicts thus consolidated that the areas of lesion in mice, monkey, and human were essentially similar.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In fact, in the mice model, it had been documented both neurons and fibers (white matter) were both targets like in this report consisting of human subjects (Mak et al, 2010; Yeung et al, 2010b). Along with structural changes, fMRI and functional studies confirmed functional and cognitive derangements (Morgan and Curran, 2006; Sun et al, 2011, 2012; Chan et al, 2012; Yu et al, 2012). This human MRI brain imaging on the ketamine addicts thus consolidated that the areas of lesion in mice, monkey, and human were essentially similar.…”
Section: Discussionmentioning
confidence: 80%
“…In the human brain, so far, few studies appeared in the literature. Our group, for example, revealed fMRI hypoactivities in the cerebellum of addicts (Chan et al, 2012). Narendran et al (2005) reported that ketamine addicts exhibited selective up-regulation of dopamine D1 receptor via biochemistry.…”
Section: Introductionmentioning
confidence: 94%
“…This is what we are waiting to see as the neonates grow up. Furthermore, many other organs, e.g., the brain, the heart and the kidneys of the progeny have to be investigated in adulthood, specifically in terms of the pathomorphological, pathophysiological, pharmacological and biochemical changes of these areas before any conclusive statements could be made [12,13,14,15,16,17,18,19,20,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of data therefore depends on being able to collect a large enough number of samples to be able to exclude false positive results. fMRI imaging has largely been conducted with humans (including normal individuals, patients, addicts, and aged individuals), as well as in animal models of addiction and aging[18,19]. In the case of patients with various diseases, the way forward for fMRI and its potential are largely still under-explored.…”
Section: Challenges and Future Directions For Fmri Studiesmentioning
confidence: 99%